Brain hyperintensity location determines outcome in the triad of impaired cognition, physical health and depressive symptoms: A cohort study in late life. (March 2016) - Murray, Alison; McNeil, Chris; Salarirad, Sima; Deary, Ian; Phillips, Louise; Whalley, Lawrence; Staff, Roger
Highlights: Illustrates how location of brain hyperintensities influences depressive outcomes. Illustrates the use of structural equation modelling with highly correlated variables. Unpicks relationships between brain hyperintensities and components of frailty. Abstract: Purpose of the study: Brain hyperintensities, detectable with MRI, increase with age. They are associated with a triad of impairment in cognitive ability, depression and physical health. Here we test the hypothesis that the association between hyperintensities and cognitive ability, physical health and depressive symptoms depends on lesion location. Design and methods: 244 members of the Aberdeen 1936 Birth Cohort were recruited to this study. 227 participants completed brain MRI and their hyperintensities were scored using Scheltens's scale. 205 had complete imaging, cognitive, physical health and depressive symptom score data. The relationships between hyperintensity location and depressive symptoms, cognitive ability and physical health were examined by correlation and structural equation analysis. Results: We found that depressive symptoms correlated with hyperintensity burden in the grey matter ( r  = 0.14, p  = 0.04) and infratentorial regions ( r  = 0.17, p  = 0.01). Infratentorial hyperintensities correlated with reduced peak expiratory flow rate ( r  = −0.26, p  < 0.001) and impaired gait ( r  = 0.13, p  = 0.05). No relationship was found between white matter and periventricular (supratentoral) hyperintensities and depressive symptoms. Hyperintensities in the supratentorial and infratentorial regions were associated with reduced cognitive performance. Using structural equation modelling we found that the association between hyperintensities and depressive symptoms was mediated by negative effects on physical health and cognitive ability. Conclusions: Hyperintensities in deep brain structures are associated with depressive symptoms, mediated via impaired physical health and cognitive ability. Participants with higher cognitive ability and better physical health are at lower risk of depressive symptoms.